Genetic Analysis and Literature Review of SNCA Variants in Parkinson's Disease - Guo, Yi; Sun, Yan; Song, Zhi; Zheng, Wen; Xiong, Wei; Yang, Yan; Yuan, Lamei; Deng, Hao (Frontiers in Aging Neuroscience, 2021)
Parkinson’s disease (PD) is the fastest growing neurodegenerative disorder. Aging, environmental and genetics are thought to be risk factors. Alpha-synuclein (SNCA), the first pathogenic gene identified in a familial form of PD, was indisputably involved as a heritable component for familial and sporadic PD. In the present study, whole exome sequencing and Sanger sequencing were performed to evaluate the association between the SNCA gene variants and PD. The genetic data of 438 clinically-diagnosed PD patients and 543 matched control populations of Han-Chinese were analyzed. Literature review of SNCA variants for 231 cases reported in 89 articles were extracted from the PubMed and Movement Disorder Society Genetic mutation database. No potentially causative variant(s) in the SNCA gene, excepting two single nucleotide nonsynonymous variants c.158C>T (p.A53V, rs542171324) and c.349C>T (p.P117S, rs145138372), were detected. There was no statistically significant difference in the genotypic or allelic frequencies for either variant between the PD group and control group (all P >0.05). No copy number variants of the SNCA gene were detected. The study results suggest that the variants in the exons of the SNCA gene may play little or no role in PD development in Han-Chinese populations. The literature review suggests that psychiatric signs and cognitive decline/dementia were more common among patients with SNCA duplication or triplication (psychiatric signs: χ2 = 7.892, P = 0.005; cognitive decline/dementia: χ2 = 8.991, P = 0.003).